MALDI-TOF MS: the proteomic approach, the future of fungal identification in India - Fonseca, Mallika; Menon, Sarala; Rahi, Praveen; Patekar, Prachi; Chowdhary, Abhay S. (International Journal of Research in Medical Sciences, 2020)
Background: India, being a country where fungal infections are rampant, is urgently in need of effective tools for early and accurate diagnosis of fungal infections. Matrix-assisted Laser Desorption Ionization Time-of-Flight Mass Spectrometry (MALDI-TOF-MS) is a recent method which has shown potential in identifying clinically important bacterial pathogens as well as clinically important fungi. The main objective of this study was to compare the utility of MALDI-TOF MS for the identification of fungi against that of conventional methods. Methods: The project was carried out in a tertiary care government hospital in India. Fifty clinical isolates comprising mainly various yeast species were subjected to conventional identification (Phenotypic) as well as MALDI-TOF-MS. Their results were further compared. Results: MALDI-TOF MS showed a high concordance with conventional methods while identifying species like C. albicans, C. tropicalis, C. parapsilosis and C. neoformans, although the concordance for species such as Rhodotorula and Trichosporon could only be matched up to genus level. Conclusions: MALDI-TOF MS-based identification is both a rapid and a viable tool for identification of clinically relevant yeast species with good correlation to conventional methods and a quick turnaround time.